Mutation-Independent Therapies for Retinal Diseases: Focus on Gene-Based Approaches - Carrella, Sabrina; Indrieri, Alessia; Franco, Brunella; Banfi, Sandro (Frontiers in Neuroscience, 2020)
Gene therapy is proving to be an effective approach to treat or prevent ocular diseases ensuring a targeted, stable, and regulated introduction of exogenous genetic material with therapeutic action. Retinal diseases can be broadly categorized into two groups, namely monogenic and complex (multifactorial) forms. The high genetic heterogeneity of monogenic forms represents a significant limitation to the application of gene-specific therapeutic strategies for a significant fraction of patients. Therefore, mutation-independent therapeutic strategies, acting on common pathways that underly retinal damage, are gaining interest as complementary/alternative approaches for retinal diseases. This review will provide an overview of mutation-independent strategies that rely on the modulation in the retina of key genes regulating such crucial degenerative pathways. In particular, we will describe how gene-based approaches explore the use of neurotrophic factors, microRNAs, genome editing and optogenetics in order to restore/prolong visual function in both outer and inner retinal diseases. We predict that the exploitation of gene delivery procedures applied to mutation/gene independent approaches may provide the answer to the unmet therapeutic need of a large fraction of patients with genetically heterogeneous and complex retinal diseases.